MXenes à la Carte: Tailoring the Epitaxial Growth Alternating Nitrogen and Transition Metal Layers - Gouveia, José D. (2022)
A high-throughput analysis based on density functional simulations underscores the viable epitaxial growth of MXenes by alternating nitrogen and metal adlayers. This is supported by an exhaustive analysis of a number of thermodynamic and kinetic thresholds belonging to different critical key steps in the course of the epitaxial growth. The results on 18 pristine N- and C-based MXenes with M2X stoichiometry reveal an easy initial N2 fixation and dissociation, where N2 adsorption is controlled by the MXene surface charge and metal d-band center and its dissociation controlled by the reaction energy change. Furthermore, formation energies indicate the plausible formation of N-terminated M2XN2 MXenes. Moreover, the further covering with metal adlayers is found to be thermodynamically driven and stable, especially when using early transition metal atoms. The most restrictive analyzed criterion is the N2 adsorption and dissociation at nearly full N-covered adlayers, which is yet achievable for almost half of the explored M2X seeds. The present results unfold the possibility of expanding, controlling, and tuning the composition, width, and structure of the MXene family.